Impact of Globalization on Corporate Social Responsibility in Multinational Companies: Exploring the Impact of Globalization on Corporate Social Responsibility in Multinational Companies (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Process of globalization has accelerated significantly since the 1980s, as many countries in the world made a transition towards democracy and free market economy. Many made a transition towards democracy and free market economy. Many governments in the developed world and global institutions like the United Nations and the World Bank contributed towards an accelerated process of international business development. With increased foreign trade, many businesses in the United States, as well as other nations, found it profitable to open offices, branch plants, distribution centers, etc., around the globe. Such companies were called multinational companies (MNCs). Other than the market and state, socio-political actors also assumed a major role in widening the scope of public policy for MNCs all over the world. The growth of MNCs and their impact worldwide has been linked to policy changes in international economics and political relations between the developed and the developing countries. In a research study, it was found that MNCs are confronted with various socio-political stakeholders . The countries studied were China, Germany, France, India, Russia and USA.